Textiles and Clothing Sustainability Sustainable Technologies - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This is the first book to deal with the innovative technologies in the field of textiles and clothing sustainability. It details a number of sustainable and innovative technologies and highlights their implications in the clothing sector. There are currently various measures to achieve sustainability in the textiles and the clothing industry, including innovations in the manufacturing stage, which is the crux of this book.
Sustainable Textile Technologies -- Sustainable Defence Textiles -- Enzymatic Washing of Denim: Greener Route for Modern Fashion.
Keywords: Manufactures; Sustainability; Industrial engineering; Production engineering; Chemistry, Technical; Environmental management; Materials -- Analysis; Machines, Tools, Processes; Sustainability; Industrial and Production Engineering; Industrial Chemistry; Environmental Management; Characterization and Analytical Technique